2014
DOI: 10.5649/jjphcs.40.734
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients with Unresectable Pancreatic Cancer Treated with Gemcitabine: A Retrospective Analysis

Abstract: Gemcitabine therapy has been the standard first-line treatment for patients with unresectable local cancer. However 1-year survival rates of less than 20% have been reported. Therefore, these results are unsatisfactory and also the prognostic factors are still not sufficiently discussed. We retrospectively analyzed the medical records of 88 patients who received gemcitabine mono-therapy for unresectable pancreatic cancer. The patient characteristics and treatment factors that may be associated with the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Fridlender et al (17) reported that neutrophils are involved in vascularisation and are associated with cancer metastasis and angiogenesis. Hatori et al (4) reported that the number of neutrophils present prior to the first GEM treatment is a prognostic factor. Additionally, it has been reported that GEM, gemcitabine; S-1, tegafur, gimeracil, and oteracil potassium; BSA, body surface area; CrCl, creatinine clearance; RDI, relative dose intensity; GEM→S-1, group, patients who received GEM as first-line therapy and S-1 as second-line therapy; GEM group, patients who received GEM as first-line therapy and did receive second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fridlender et al (17) reported that neutrophils are involved in vascularisation and are associated with cancer metastasis and angiogenesis. Hatori et al (4) reported that the number of neutrophils present prior to the first GEM treatment is a prognostic factor. Additionally, it has been reported that GEM, gemcitabine; S-1, tegafur, gimeracil, and oteracil potassium; BSA, body surface area; CrCl, creatinine clearance; RDI, relative dose intensity; GEM→S-1, group, patients who received GEM as first-line therapy and S-1 as second-line therapy; GEM group, patients who received GEM as first-line therapy and did receive second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that second-line treatment with S-1 monotherapy is associated with a better prognosis in APC patients (4,(12)(13)(14). Similarly, this study has demonstrated that it is important to use GEM and S-1 for the treatment of APC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation